A novel C-terminal modification method enhanced the yield of human papillomavirus L1 or chimeric L1-L2 virus-like particles in the baculovirus system - Ma, Mingrao; Xia, Baicheng; Wang, Zhirong; Hao, Yaru; Zhang, Ting; Xu, Xuemei (Frontiers in Bioengineering and Biotechnology, 2023)
Human papillomavirus (HPV) major capsid protein L1 virus-like particles (VLPs) produced in the baculovirus system showed excellent safety and immunogenicity, but the relatively high production cost stands as a substantial barrier to extensive commercialization, especially in producing multivalent vaccines. Here, a novel method, C-terminal basic amino acid (aa) substitution, was developed for increasing VLP and chimeric VLP (cVLP) production in this system. A series of mutants of five HPV types, including three L1 VLPs (6L1, 11L1, 52L1) and two L1-L2 cVLPs (16L1-33L2, 58L1-16L2), were constructed. We found that most mutants exhibited higher protein expression in Sf9 cells, among which the yields of the superior mutants, 6L1CS4, 11L1CS3, 52L1m4∆N13CS1, 16L1-33L2 CS1, and 58L1-16L2 CS3, were up to 40, 35, 20, 35 and 60 mg/L, which respectively increased by 4.2-, 7.3-, 5-, 2.5- and 3.4-fold, and they also showed robust immunogenicity and great stabilities. Additionally, we found that the increased level of steady-state mRNA may play a crucial role in promoting L1 protein expression. Our results demonstrated that this novel method was cost-effective and can be used to reduce the production costs of L1 VLPs and L1-L2 cVLPs to develop broadly protective and affordable multivalent HPV vaccines.